Economic Consequences of Ill-Health in Rural Ethiopia. Issue 2 (1st July 2021) - Yilma, Zelalem; Mebratie, Anagaw Derseh; Sparrow, Robert; Dekker, Marleen; Alemu, Getnet; Bedi, Arjun S.
ABSTRACT: We use three years of household panel data to analyze the effects of ill-health on household economic outcomes in rural Ethiopia. We examine the immediate effects of various ill-health measures on health expenditure and labor supply, the subsequent coping responses, and finally the effect on income and consumption. We find evidence of substantial economic risk in terms of increased health expenditure and reduced agricultural productivity. Households are able to smooth consumption by resorting to intra-household labor substitution, borrowing and depleting assets. However, maintaining current consumption through borrowing and depletion of assets is unlikely to be sustainable and displays the need for health financing reforms and safety nets that reduce the financial consequences of ill-health.